Straum's outline of Theory and problems of chemistry foundations - David E Goldberg (McGraw-Hill, 1991)
This book is designed to help students who have little or no chemistry bacground to well in their first chemistry course. It also help students develop both problem-solving skills and skill in precise reading and interpreting scientific problems and questions. The book often presents problems in parts, then asks the same question as an entity. It provides some figures which have proved helpful to a generation of students